PUTUSAN HAKIM DALAM MENJATUHKAN PIDANA TERHADAP ANAK PELAKU TINDAK PIDANA KEPEMILIKAN SENJATA API ATAU BENDA TAJAM - Nanda Anggraeni Effendy Jefri Saputra (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2021)
One form of criminal acts of possession of weapons committed by children or children who are in conflict with the law is in Decision Number: 14/Pid.Sus-Anak/2019/PN Gdt. The research method uses a normative and empirical juridical approach. Sources of normative and empirical data. Collecting data through library research and field research. The data analysis used was qualitative juridical. The results of the research and discussion show that the factors causing the child to be the perpetrator of a criminal act of possession of firearms or sharp objects based on Decision Number: 14/Pid.Sus-Anak/2019/PN Gdt are 1 (one) sharp weapon blade with a wooden handle and a wooden cover is the property of Son HA Bin YH who was brought with the aim to protect themselves. Criminal responsibility for children as perpetrators of criminal possession of firearms or sharp objects based on Decision Number: 14/Pid.Sus-Anak/2019/PN Gdt is to impose a 4 (four) month imprisonment and charge the child to pay a court fee of IDR 2,000 (two thousand rupiah). Judges' legal considerations in imposing criminal sanctions on children as perpetrators of criminal acts of possession of firearms or sharp objects based on Decision Number: 14/Pid.Sus-Anak/2019/PN Gdt are in accordance with the provisions of the applicable law. What is burdensome is that the child's actions are disturbing society, while what mitigates is the child admits frankly and regrets his actions and promises not to repeat it and the child has never been punished.